2005
DOI: 10.1007/s00424-005-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

VIP receptors control excitability of suprachiasmatic nuclei neurones

Abstract: The role of vasoactive intestinal polypeptide (VIP) receptors on excitable properties of neurones in slices acutely prepared from the suprachiasmatic nuclei (SCN) of wild-type (WT) and VPAC(2)-receptor-deficient (Vipr2 ( -/- )) mice was studied under voltage clamp with the use of patch-clamp recording in the whole-cell configuration. The resting membrane potential in Vipr2 ( -/- ) neurones was significantly hyperpolarised as compared to WT cells (-60+/-7 vs -72+/-6 mV, p<0.01). Bath application of 100 nM VIP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 56 publications
10
36
0
Order By: Relevance
“…The effect of potassium depolarization to increase VP gene transcription in TTX that was blocked by inhibitors of calcium ion influx through voltage-gated calcium channels (Fig. 9, Cd, nimodipine) is consistent with this hypothesis and with reports describing voltage-gated calcium channels as an important factor in the regulation of circadian rhythms in the SCN (Pennartz et al, 2002;Lundkvist et al, 2005;Pakhotin et al, 2006). Inhibition by the CaM general protein kinase inhibitor (KN62) but not by a specific CaM protein kinase II inhibitor (KN93) suggests that this signal transduction pathway might use CaM IV (Obrietan et al, 2002).…”
Section: Depolarization-induced Calcium Ion Signals Regulate Vp Transsupporting
confidence: 90%
See 1 more Smart Citation
“…The effect of potassium depolarization to increase VP gene transcription in TTX that was blocked by inhibitors of calcium ion influx through voltage-gated calcium channels (Fig. 9, Cd, nimodipine) is consistent with this hypothesis and with reports describing voltage-gated calcium channels as an important factor in the regulation of circadian rhythms in the SCN (Pennartz et al, 2002;Lundkvist et al, 2005;Pakhotin et al, 2006). Inhibition by the CaM general protein kinase inhibitor (KN62) but not by a specific CaM protein kinase II inhibitor (KN93) suggests that this signal transduction pathway might use CaM IV (Obrietan et al, 2002).…”
Section: Depolarization-induced Calcium Ion Signals Regulate Vp Transsupporting
confidence: 90%
“…This suggested that there might also be a depolarization-evoked, presumably calcium iondependent, pathway that could increase VP gene transcription in TTX. It should be noted here that the extent and synchrony of spike activity in the SCN are highly regulated by the VPAC2 receptor and are dysregulated in the Vipr2 Ϫ/Ϫ SCN (Reed et al, 2002;Cutler et al, 2003;Piggins and Cutler, 2003;Pakhotin et al, 2006). Therefore, these two mechanisms are not entirely independent.…”
Section: Depolarization-induced Calcium Ion Signals Regulate Vp Transmentioning
confidence: 88%
“…2A). This prediction is in agreement with data showing that VIP is excitatory (Pakhotin et al, 2006) and that increasing GABA always generated greater IPSC in the core of the SCN (Albus et al, 2005). GABA depletion increased firing rates in agreement with experimental studies (Gribkoff et al, 2003; Shirakawa et al, 2000).…”
Section: Resultssupporting
confidence: 92%
“…In particular, Per1 transcription positively correlates with firing rate in a linear fashion in Per1:GFP (green fluorescent protein) mice (113). In vasoactive intestinal peptide receptor 2 (VPAC2) receptor-deficient mice, Per1, Per2, and Cry1 gene expression is attenuated in the SCN (114), and similar blunted rhythms are observed in the cellular excitability in these animals (115)(116)(117). However, it is unclear whether all extra-SCN brain regions translate clock gene expression cycles into physiologically relevant firing rate rhythms.…”
Section: Multiple Brain Clocks: Multiple Clock Mechanisms?mentioning
confidence: 99%